Introduction to the SAVE study (2011–15): Streptococcus pneumoniae serotyping and antimicrobial susceptibility: Assessment for Vaccine Efficacy in Canada after the introduction of PCV-13. (2nd July 2018) - Zhanel, George G; Adam, Heather J
Abstract: Streptococcus pneumoniae continues to be an important bacterial pathogen associated with invasive (e.g. bacteraemia) and non-invasive (e.g. community-acquired respiratory tract) infections worldwide. Surveillance studies conducted nationally and globally can assist in determining trends across geographical areas and allow comparisons between countries. SAVE is an ongoing, annual, national study focused on characterizing invasive isolates of S. pneumoniae obtained across Canada. This Supplement documents the initial 5 years of the SAVE study (2011–15) during which 6207 invasive isolates of S. pneumoniae were evaluated. The three manuscripts in this Supplement provide a comprehensive examination of the changing patterns of invasive S. pneumoniae obtained across Canada over a 5 year period. The data highlight the evolution of S. pneumoniae antimicrobial resistance and multidrug resistance, serotype distribution, genotypic relatedness and virulence under pressure by vaccination and antimicrobial usage. This allows both clinicians and researchers nationally and globally to view the current status of invasive pneumococcal infections in Canada.